1994
DOI: 10.1152/jn.1994.72.2.999
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic integration in a model of cerebellar granule cells

Abstract: 1. We have developed a compartmental model of a turtle cerebellar granule cell consisting of 13 compartments that represent the soma and 4 dendrites. We used this model to investigate the synaptic integration of mossy fiber inputs in granule cells. 2. The somatic compartment contained six active ionic conductances: a sodium conductance with fast activation and inactivation kinetics, gNa; a high-voltage-activated calcium conductance, gCa(HVA); a delayed potassium conductance, gK(DR); a transient potassium condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
117
1
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(125 citation statements)
references
References 0 publications
6
117
1
1
Order By: Relevance
“…Granule cells can be induced to fire at frequencies up to 200 Hz in slice preparations (Gabbiani et al, 1994), and in the present study no depletion in the amount of transmitter release is observed with repetitive trains of stimuli (Fig. 5).…”
Section: Vesicle Pools During High-intensity Stimulation In Granule Csupporting
confidence: 66%
“…Granule cells can be induced to fire at frequencies up to 200 Hz in slice preparations (Gabbiani et al, 1994), and in the present study no depletion in the amount of transmitter release is observed with repetitive trains of stimuli (Fig. 5).…”
Section: Vesicle Pools During High-intensity Stimulation In Granule Csupporting
confidence: 66%
“…Because the time-averaged voltage in a firing neuron remains approximately constant (close to threshold potential), introducing a shunting conductance results in constant-current offset. This has been confirmed theoretically (Gabbiani et al, 1994;Holt and Koch, 1997) and experimentally with excitation mimicked by constant-current injection (Brickley et al, 1996;Chance et al, 2002;Ulrich, 2003). However, in vivo, neurons are bombarded by a noisy, stochastic input (Paré et al, 1998;Destexhe and Paré, 1999;Destexhe et al, 2001), which influences I-O gain and increases the input range of a neuron (Hô and Destexhe, 2000;Doiron et al, 2001;Chance et al, 2002;Fellous et al, 2003;Wolfart et al, 2005;Higgs et al, 2006).…”
Section: Introductionmentioning
confidence: 67%
“…Since clustered extrasynaptic GABA A receptors mediate larger tonic currents, it is possible that, under either physiological or pathological conditions, receptor clustering can modulate tonic inhibition and in turn influence synaptic efficacy and integration (6,10,13,14,20).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas synaptic GABA A receptors are involved in phasic inhibition (1), extrasynaptic ones are responsible for tonic inhibition (2)(3)(4)(5)(6)(7)(8)(9). Tonic inhibition is due to persistent inhibitory conductance that contributes to "signal integration" in the brain since it sets the threshold for action potential generation (10,11) and shunts excitatory synaptic inputs (2,(12)(13)(14)(15). This conductance is maintained by "ambient" GABA, which represents the amount of neurotransmitter present in the extracellular space.…”
mentioning
confidence: 99%